2009
DOI: 10.1177/105678790901800103
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Tattling on Teachers: Policy Attitude and Tenure's Influence on Peer Reporting of Unethical Behavior

Abstract: Teachers’ cheating on high-stakes standardized tests is a serious problem for public schools. This study examined the influence of school tenure and policy attitudes about standardized testing on teachers’ decisions to report a peer for violating testing protocol. In sum, 330 Texas school teachers responded to a survey that included a scenario depicting a teacher violating standardized testing protocol. Analysis of variance revealed that teachers with negative and moderate attitudes about standardized testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Ning et al (2017) have pointed out that educational level affects employees' unethical behavior as well. Moreover, Richardson et al (2009) have emphasized that organizational tenure is an important factor that determines whether individuals engage in (un)ethical behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Ning et al (2017) have pointed out that educational level affects employees' unethical behavior as well. Moreover, Richardson et al (2009) have emphasized that organizational tenure is an important factor that determines whether individuals engage in (un)ethical behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, it has often been debated if the use of standardized testing improves education and whether tests are fair and objective tools for measuring students' learning. The controversies over standardized testing include, among others, lack of inclusiveness (Pohl et al, 2016), narrowing the curriculum by teaching to the test rather than other skills (Linn, Herman, 1997 in Bhattacharyya, Clark, 2013;Richardson, Wheeless, 2009;Wallace, Irons, 2010), rise in anxiety level of students and teachers (Smith, 1991) as well as pushing students out of school and driving teachers out of the profession (Hout, Elliott, 2011in Evans, Howarth, 2019. It is to be observed that the current design of standardized tests hardly ever recognizes the needs of SEN students and their cognitive limitations.…”
Section: Standardized Testingmentioning
confidence: 99%